Penatalaksanaan Holistik Penyakit Tonsilitis Akut pada Anak Perempuan Usia Enam Tahun di Puskesmas Pasar Ambon melalui Pendekatan Kedokteran Keluarga - Asadha, Syahfa Alzena; Ernawati, Tutik (CV. Jasa Sukses Abadi, 2024)
Tonsillitis can strike any age but is more common in children. Inflammation of the tonsils can be caused by bacteria or viruses. Inflammation of the tonsils will result in enlargement which causes difficulty swallowing or feels like there is a lump in the throat. Enlarged tonsils can also cause other symptoms such as hoarseness (muffled voice) or even breathing problems in severe cases. If there is no complete healing of the tonsils, recurrent infections can occur. Applying the principles of family medicine services and carrying out holistic management based on a framework for solving patient problems with a patient-centered, family-focused, and community-oriented approach based on Evidence-Based Medicine. This study is a case report using primary data obtained through history taking, physical examination, and home visits to complement family data, and psychosocial and environmental data. Secondary data was obtained from patient medical records. Patient An. N aged six years old with complaints of swallowing pain since four days ago. Patients have a habit of consuming iced drinks and light snacks which may be unhygienic and can be a risk factor for infection. Holistic management with a family doctor approach has been carried out for An. N aged six years with Acute Tonsillitis which was adjusted based on the initial holistic diagnosis. Before the intervention, the patient and family are given a pretest to measure the patient's level of knowledge regarding the disease they are suffering from. During the intervention, the family is explained about the disease she is suffering from using media in the form of posters, and the family is given education regarding the importance of treatment and how to prevent the disease. At the last visit a posttest was given to the family with the results being a significant increase in knowledge about the disease they were suffering from and awareness of the importance of changing patient habits.